Penyerahan Protokol Minuta Akta oleh Notaris yang Berpindah Kedudukan Berdasarkan Undang-Undang Nomor 2 Tahun 2014 tentang Perubahan atas Undang-Undang Nomor 30 Tahun 2004 tentang Jabatan Notaris (Studi di Kabupaten Deli Serdang) - Shervira Chariss Wong; Tony; Rosnidar Sembiring (CV Rewang Rencang, 2025)
The Notary Protocol, as a state archive, must be safeguarded, preserved, and maintained. The Minuta Akta, as an integral part of the Notary Protocol, carries a crucial function as the basis for issuing copies of deeds; therefore, its existence must be guaranteed. This study analyzes the following issues: the mechanism for submitting and receiving the Notary Protocol when a notary relocates, including the legal responsibility for Minuta Akta that are not submitted; the forms of legal sanctions imposed on notaries who fail to submit the protocol completely after relocation; and the available legal remedies for parties requiring a Minuta Akta that forms part of the Notary Protocol. This research employs a normative juridical method. The results of the study show that the mechanism for submitting the Notary Protocol is regulated under Article 63 of the Notary Office Law (UUJN-P) and Minister of Law and Human Rights Regulation No. 22 of 2025. The submission of the Notary Protocol is formalized through the signing of a Handover Report (Berita Acara Serah Terima) witnessed by the Regional Supervisory’ Council (MPD).